ANALISIS PENGARUH BIAYA PROMOSI TERHADAP VOLUME PENJUALAN PADA PT. INDRAPURA ASSURANCE PEKANBARU - I Putu Indra Surya; Sri Restuti; Aida Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
PT. Indrapura Pekanbaru Assurance is one of the non-bank financial institutions, where their activities in the face of competition from other non-bank financial institutions to market their services to the public. To cope with the competition, it is necessary to seize the marketing strategy for its target market as much as possible to anticipate any changes in the marketing environment. The purpose of this study is to see the effect of the cost of advertising, individual sales, publicity and direct marketing to the volume of sales at PT. Indrapura Assurance Pekanbaru.The types and sources of data used in this research is secondary data, ie data obtained by the authors of the company in the form of marketing promotion cost data and the number of policies sold in 2010-2015 as well as some other data assessed as having relevance to this study. Then the data will be analyzed using ANOVA with SPSS 21.The result showed that the variables simultan eously advertising, individual sales, publicity and marketing directly affect the volume of sales. Partially get the result that the cost of advertising, sales and marketing individuals direct positive effect on the sales volume. While publicity is not a positive effect on sales volume. Values obtained adjsuted R square of 0.995 which means the percentage of the influence of advertising, personal selling, publicity and marketing directly affect the volume of sales at PT. Pekanbaru Indrapura Insurance of 99.5%.Keywords : Advertising, Personal Selling, Publicity, Direct Marketing and Sales Volume